Optimization of the Production Process of Clinical-Grade Human Salivary Gland Organoid-Derived Cell Therapy for the Treatment of Radiation-Induced Xerostomia in Head and Neck Cancer - Jacoba van Zanten; Annelies Jorritsma-Smit; Hans Westra; Mirjam Baanstra; Anne de Bruin-Jellema; Derk Allersma; Bahez Gareb; Rob P. Coppes (MDPI AG, 2024)
Head and neck cancer is a common cancer worldwide. Radiotherapy has an essential role in the treatment of head and neck cancers. After irradiation, early effects of reduced saliva flow and hampered water secretion are seen, along with cell loss and a decline in amylase production. Currently, there is no curative treatment for radiation-induced hyposalivation/xerostomia. This study aimed to develop and optimize a validated manufacturing process for salivary gland organoid cells containing stem/progenitor cells using salivary gland patient biopsies as a starting material. The manufacturing process should comply with GMP requirements to ensure clinical applicability. A laboratory-scale process was further developed into a good manufacturing practice (GMP) process. Clinical-grade batches complying with set acceptance and stability criteria were manufactured. The results showed that the manufactured salivary gland-derived cells were able to self-renew, differentiate, and show functionality. This study describes the optimization of an innovative and promising novel cell-based therapy.